2018
DOI: 10.1104/pp.18.01190
|View full text |Cite
|
Sign up to set email alerts
|

Heterohexamers Formed by CcmK3 and CcmK4 Increase the Complexity of Beta Carboxysome Shells

Abstract: Bacterial microcompartments (BMCs) encapsulate enzymes within a selectively permeable, proteinaceous shell. Carboxysomes are BMCs containing ribulose-1,5-bisphosphate carboxylase oxygenase and carbonic anhydrase that enhance carbon dioxide fixation. The carboxysome shell consists of three structurally characterized protein types, each named after the oligomer they form: BMC-H (hexamer), BMC-P (pentamer), and BMC-T (trimer). These three protein types form cyclic homooligomers with pores at the center of symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 57 publications
9
65
0
Order By: Relevance
“…paralogs could be demonstrated. The formation of hetero-hexamers between CcmK3 and CcmK4 from Synechococcus elongatus PCC7942 (Syn7942) could be shown too, thus confirming and complementing results obtained on the same proteins and on paralogs from Halothece PCC 7418 (Hal7418) [34]. Such observations were reasoned on the basis of sequence identities and compensatory effects for residues implicated in inter-subunit contacts, also by means of dynamic simulations using homology models.…”
Section: Experimental Compatibilities Between Ccmk1 and Ccmk2 As Welsupporting
confidence: 79%
See 2 more Smart Citations
“…paralogs could be demonstrated. The formation of hetero-hexamers between CcmK3 and CcmK4 from Synechococcus elongatus PCC7942 (Syn7942) could be shown too, thus confirming and complementing results obtained on the same proteins and on paralogs from Halothece PCC 7418 (Hal7418) [34]. Such observations were reasoned on the basis of sequence identities and compensatory effects for residues implicated in inter-subunit contacts, also by means of dynamic simulations using homology models.…”
Section: Experimental Compatibilities Between Ccmk1 and Ccmk2 As Welsupporting
confidence: 79%
“…Despite well expressed, the low solubility of Syn6803 K3 precluded the investigation of its solution behavior or attempts to elucidate its crystal structure. To understand whether this behavior could be linked to an incorrect folding of the K3 monomer or to the presence of residues incompatible with oligomerization, the amino acid sequence was first aligned with those of other Syn6803 paralogs or of CcmK from Syn7942 and Hal7418 species recently studied by Kerfeld and coworkers [34] (Fig. 4A).…”
Section: Sequence-structural Considerations For the Formation Of Ccmkmentioning
confidence: 99%
See 1 more Smart Citation
“…While the abundance of most of the structural components varies, the ratio of CcmK4 and CcmK3 is relatively unaffected (ranging from 3.6 to 4.1, Supplemental Table 5) under the tested growth conditions, implying their spatial colocalization within the carboxysome shell ( Figure 6A). It is reminiscent of the recent observation that CcmK3 and CcmK4 can form a heterohexameric complex with a 1:2 stoichiometry and further form dodecamers in a pH-dependent manner (Sommer et al, 2019). The ccmK3 and ccmK4 genes are located in the same operon that is distant from the ccm operon and they may have different expression regulation compared with other carboxysome components (Rae et al, 2012;Sommer et al, 2017).…”
mentioning
confidence: 99%
“…A question that still remains regarding the PduBB' is that whether the combination is a heterotrimer or a dimer of trimers of PduB and PduB'. Recently, Sommer et al 2019 have shown that in betacarboxysomes, shell proteins Ccmk3 and Ccmk4 exist as heterotrohexamers and alter the permeability properties of carboxysome shell (39). This suggests that shell protein combination can have a significant role in the functioning of MCPs.…”
Section: Discussionmentioning
confidence: 99%